How do we transfuse blood components in cirrhotic patients undergoing gastrointestinal procedures?. Issue 4 (15th February 2016) - Yates, Sean G.; Gavva, Chakri; Agrawal, Deepak; Sarode, Ravi
Abstract : The liver plays a pivotal role in hemostasis. Consequently, patients with cirrhosis frequently demonstrate abnormal coagulation profiles on routine laboratory tests. These tests mainly reflect decreased procoagulant proteins. However, in cirrhosis, complex changes also occur in anticoagulant and fibrinolytic pathways. Recent evidence demonstrates that patients with cirrhosis exist in a state of hemostatic rebalance. Accordingly, routine tests inadequately represent hemostatic alterations in these patients. Unfortunately, these tests are regularly used to guide the transfusion of blood components with the assumption that they will correct laboratory abnormalities and improve hemostasis in a bleeding patient or prevent excessive bleeding following a procedure. With an absence of both accurate laboratory testing to assess hemostasis and evidence‐based guidelines to direct the transfusion of blood components, management of patients with cirrhosis poses a significant challenge to clinicians. Therefore, we developed multidisciplinary guidelines for the periprocedural transfusion of blood components in patients with cirrhosis based on concurrent evidence and personal experience at our medical center.